Pockets of hope: Cases of linguistic flexibility in the classroom - Leah Durán; Kathryn I. Henderson (EuroAmerican Journal of Applied Linguistics and Languages, 2018)
This study adds to the small but growing body of work demonstrating the instructional potential of linguistic flexibility and hybridity to support student learning. Our findings from two elementary classrooms illustrate the way that translanguaging pedagogy contributes to students’ understanding of content-area material as well as their mastery of language arts skills. Student language practices described as reflecting academic language, language variation, and code-switching represent three domains that are often talked about separately. We consider the ways both focal teachers created spaces for students to draw on linguistic resources across these domains. In our discussion of the findings and their implications, we attempt to unite these perspectives in order to extend current understandings about translanguaging pedagogy and highlight ways to value and employ a broader spectrum of language practices for academic purposes.